Risk factors for non‐gastric‐cancer‐related death after gastrectomy in elderly patients - Michihisa Iida; Shigeru Takeda; Chiyo Nakashima; Mitsuo Nishiyama; Yusaku Watanabe; Nobuaki Suzuki; Shigefumi Yoshino; Yuki Nakagami; Tsuyoshi Tanabe; Hiroaki Nagano (Annals of Gastroenterological Surgery, 2022)
Abstract Aim To identify preoperative factors, especially other diseases that cause death, that are associated with the prognosis of gastrectomy in elderly patients with gastric cancer. Methods This retrospective study included a total of 211 consecutive patients aged ≥75 years who underwent radical gastrectomy due to gastric cancer. Time‐dependent receiver operating characteristic curve analysis was performed to determine the optimal cutoff values for various perioperative factors. Risk factors for the overall survival and death from other diseases were analyzed using the Cox proportional hazards model. Results Among the all perioperative factors, sex, neutrophil‐to‐lymphocyte ratio, skeletal muscle mass index, and lymph node dissection in accordance with guidelines or not extracted as independent risk factors for death from other diseases. In an analysis restricted to the preoperative factors, sex, neutrophil‐to‐lymphocyte ratio, and skeletal muscle mass index of the patients were extracted as independent risk factors for death from other diseases and overall survival. We divided the patients into four groups according to the number of preoperative risk factors for death from other diseases and found that the 5‐year non‐gastric‐cancer‐related survival was different among the four groups (risk factor 0, 91.7%; risk factor 1, 83.3%; risk factor 2, 56.3%; risk factor 3, 27.2%; P < 0.001). Conclusion Male sex, low skeletal muscle mass index, and high neutrophil‐to‐lymphocyte ratio are risk factors for non‐gastric‐cancer‐related death and the overall survival of elderly patients undergoing gastrectomy. Cautious treatment strategies are needed for elderly gastric cancer patients with many risk factors.